Case report: “Major fetal cardiac pathology associated with a novel CTNND1 mutation” - Zhao, Xuliang; Li, Xu; Sun, Weiwei; Wei, Zhuojun; Yu, Min; Zhang, Man; Tian, Ruixia (Frontiers in Pediatrics, 2023)
Background: The p120-ctn protein, encoded by CTNND1, is involved in intercellular connections and regulates epithelial–mesenchymal transformation. CTNND1 mutations can lead to blepharocheilodontic syndrome (BCDS). Increasing evidence shows that although BCDS mainly manifests as craniofacial and oral deformities, it can also present as congenital heart disease, limb deformities, and neurodevelopmental disorders. Case Description: We report a prenatal case of a major cardiac malformation at 24+3 weeks of gestation. Ultrasound examination revealed a hypoplastic left ventricular, aortic coarctation, and a ventricular septal defect. Genetic analysis of the fetal tissues showed the presence of a novel mutation in CTNND1 (NM_001085458.2: c.566_c.567insG; p.Pro190fs*15), which may lead to premature termination of protein coding, while both the parents harbored wild-type CTNND1. To date, only 15 CTNND1 mutations have been reported in 19 patients worldwide, of which approximately 31% (6/19) had a cardiac phenotype. Conclusion: To the best of our knowledge, this is the first case report of fetal complicated cardiac malformations caused by this CTNND1 mutation. Our findings provide new clinical references for prenatal diagnosis and suggest an important role for CTNND1 in early cardiac development.